Prioritizing Service Quality Levers in a Business Hotel: Empirical Evidence from SERVQUAL - Hajar Dewantara; Andika Isma; Soussou Raharimalala (Global Research Collaboration, 2025)
This study investigates whether the SERVQUAL dimensions tangibles, reliability, responsiveness, assurance, and empathy—explain customer satisfaction in an independent full-service hotel and identifies the most influential levers. A cross-sectional survey of 100 staying guests recruited via accidental (intercept) sampling was administered using validated Likert-scale items. Construct validity and reliability were established prior to hypothesis testing. Multiple regression with standardized coefficients was employed to estimate the partial effects of each dimension and to assess their relative importance. Results indicate that all dimensions exhibit positive associations with satisfaction; empathy emerges as the strongest predictor, followed by assurance, reliability, and responsiveness, while tangibles show the weakest effect. These findings highlight the primacy of human-contact factors—attentiveness, credibility, and individualized care in shaping satisfaction within hospitality settings, while signaling improvement opportunities in physical cues and facilities. Managerially, the hotel should sustain strengths in empathy and assurance (e.g., staff sensitivity, clear guarantees, consistent fulfillment of promises) and systematically uplift tangibles through visible quality cues, facility upkeep, and amenity standards. The study contributes firm-level evidence to the hospitality literature by clarifying the relative weights of SERVQUAL dimensions for satisfaction and by underscoring that people-centric capabilities remain decisive even when tangible attributes lag.